Dorsal root entry zone (DREZ) localization using direct spinal cord stimulation can improve results of the DREZ thermocoagulation procedure for intractable pain relief - Tomás, Robert; Haninec, Pavel (Pain, 2005)
The dorsal root entry zone (DREZ) thermocoagulation for intractable pain after brachial plexus avulsion was performed in 21 patients. Good results in pain relief (relief of more than 75% of preoperative pain) were achieved in 62% of patients, whereby fair results (relief of 25-75% of preoperative pain) in 38% of patients. There was no patient with poor result (relief of less than 25% of preoperative pain). Complication rate was 14%. The whole patient population was subdivided into two groups (Group 1 and Group 2). Direct spinal cord bipolar stimulation and registration with the goal to localize DREZ was performed in the Group 2 consisting of 12 patients (n=12). The point on the spinal cord surface where no response after stimulus of low intensity was obtained was the site (the posterolateral sulcus) we identified as the most suitable point for the placement of radiofrequency thermocoagulation electrode. Comparing with the Group 1 consisting of nine patients (n=9), where the localization of DREZ by evoked potentials was not performed, significantly better effect of pain relief was recorded (P<0.05, odds ratio 10). There was no statistically significant difference (P>0.7) in complication rate in Group 1 and Group 2. Described electrophysiological technique is very helpful in identifying of DREZ and, in combination with microsurgical technique, can create DREZ thermocoagulation more effective.
Keywords: dospělí; elektrokoagulace; elektrická stimulace; Electric Stimulation; Female; Pain Measurement; Adult; ženské pohlaví; Spinal Nerve Roots; lidé; Pain, Intractable; Electrocoagulation; míšní kořeny; měření bolesti; retrospektivní studie; Male; Aged; evokované potenciály; Evoked Potentials; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; nezvladatelná bolest; Humans